2006
DOI: 10.1309/98ye9e442ar7lx2x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Renal Cell Carcinoma

Abstract: We describe the clinical features, outcome, pathology, cytogenetics, and molecular aspects of 13 pediatric papillary renal cell carcinomas during a 19-year period. Seven cases (54%) had translocations involving Xp11.2 (TFE3). They were identified by cytogenetic, molecular, and/or immunohistochemical analyses. All Xp11.2+ translocations were TFE3+ by immunostaining. Cytogenetic and/or polymerase chain reaction analyses identified 3 cases with t(X17) and 1 case with t(1;17), and all had additional translocations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 61 publications
2
37
1
Order By: Relevance
“…Some reports indicated that a proportion of Xp11.2 RCCs developed in patients who had a previous history of cytotoxic chemotherapy [18,19]. Indeed, our case had a history of AML and received myeloablative chemotherapy.…”
Section: Discussionmentioning
confidence: 75%
“…Some reports indicated that a proportion of Xp11.2 RCCs developed in patients who had a previous history of cytotoxic chemotherapy [18,19]. Indeed, our case had a history of AML and received myeloablative chemotherapy.…”
Section: Discussionmentioning
confidence: 75%
“…According to the literature, isolated masses with small diameters (<7 cm) and well-defined boundaries are regarded as appropriate candidates for NSS [17, 20, 27, 28], which is based on the finding that tumors with small diameters and clear rims predicate positive prognosis. From our statistical outcomes, both small diameters (<7 cm) and clear boundaries were protective factors for prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, APE-1 has been shown to interact with cAMP response element-binding protein and activate Hif1α and its own expression. All of these proteins form a transcription activation complex to activate VEGF under hypoxia conditions (Ramphal et al ., 2006). cAMP response element-binding protein binds p300 or CBP to modify chromatin structure for transcription activation (Rouaux et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%